Antiphospholipid syndrome as a cause for recurrent myocardial infarction. (September 2013) - Snipelisky, David; Stancampiano, Fernando; Shapiro, Brian
Abstract: Introduction: This case describes a patient who suffered three myocardial infarctions over a two-week period. Testing confirmed thrombophilia as the etiology. Case: A 55-year old male initially presented to the emergency department with a complaint of chest pain. Testing showed an elevated troponin at 2.2 ng/ml and ST elevations on electrocardiogram. The patient was transferred to the cardiac catheterization laboratory and a drug-eluting stent was placed. One day after the initial stent placement, in-stent thrombosis of the drug-eluting stent was discovered. Angioplasty and aspiration thrombectomy were performed, and the patient was released from the hospital three days later. 72 h after his discharge, the patient returned to the emergency department due to recurrent chest pain and diaphoresis. Shortly after arrival he became unresponsive and telemetry showed ventricular tachycardia which resolved with cardioversion. Reocclusion of the right coronary artery was again noted in the catheterization laboratory and three bare metal stents were placed. Laboratory testing found presence of anticardiolipin antibody and evidence of PT20201A mutation. Conclusion: Hypercoagulable states, although an uncommon cause of myocardial infarction, should be considered when investigating the etiology of recurrent coronary events. Prompt treatment is important in the prevention of future occurrences.